Prosociality from the perspective of environmental psychology - Klein, Sina; Nockur, Laila; Reese, Gerhard (Current opinion in psychology, 2022)
Pro-environmental behavior, a form of prosocial behavior that ultimately benefits all humanity, is essential for addressing climate change. This review presents pro-environmental behavior in a social dilemma framework describing how non-aligned interests in nested groups (e.g. smaller groups with interests opposing the interests of a superordinate group entailing the smaller groups) and unequal opportunities (e.g. differential access to resources) constitute barriers to pro-environmental behavior. We then summarize recent literature on three ways in which these barriers could be addressed. Specifically, we review how individual and conflicting interests might be overcome and benefits for the collective can be achieved by (1) collective action and global identities, (2) applying insights from another global crisis, the COVID-19 pandemic, and (3) a shift to research methods that consider the nested structure of and unequal opportunities within global crises as well as high-impact actions. Taken together, these approaches might foster one form of prosociality, pro-environmental behavior, that is desperately needed in the pursuit of sustainability.